International communication of Indonesia-China in the frame of yospan dance diplomacy - Dani Fadillah; Wajiran Wajiran; Uspal Jandevi (International Journal of Visual and Performing Arts, 2021)
Diplomacy and communication between countries have real implications for intercultural encounters, and this position must be seen as an event that is not value-free. Indonesian people residing in China, primarily students, have informal tasks with a national mission, which plays an essential role in cultural communication and cultural diplomacy. They are Indonesian students who have artistic abilities and every year they always put on performances, one of which is dance performances. This study describes how a traditional dance from Papua, Yospan, can be used as diplomacy between Indonesia and China. This research was conducted using a qualitative approach; each data obtained will be analyzed using international communication theory and soft diplomacy. This study found that traditional dances and literature in cultural missions are one of the tools of cultural diplomacy that can be used to change the stereotypes and prejudices of foreigners about Indonesia. The conclusion in this study shows that in international communication, traditional culture is a powerful way to build diplomacy. Therefore, this study recommends that the government supports Indonesian students in establishing Indonesian cultural centers in various friendly countries where Indonesian students study.